Heat stress during seed filling interferes with sulfur restriction on grain composition and seed germination in oilseed rape (Brassica napus L.) - Brunel-Muguet, Sophie; D'Hooghe, Philippe; Bataillé, Marie-Paule; Larré, Colette; Kim, Tae-Hwan; Trouverie, Jacques; Avice, Jean-Christophe; Etienne, Philippe; Dürr, Carolyne (Frontiers in Plant Science, 2015)
In coming decades, increasing temperatures are expected to impact crop yield and seed quality. To develop low input systems, the effects of temperature and sulfur (S) nutrition in oilseed rape, a high S demanding crop, need to be jointly considered. In this study, we investigated the effects of temperatures (High Temperature (HT), 33 °C/day, 19 °C/night vs. Control Temperature (Ctrl T), 20°C/day, 15°C/day) and S supply (High S (HS), 500 µm SO42- vs. Low S (LS), 8.7 µM SO42-) during seed filling on (i) yield components (seed number, seed dry weight (SDW) and seed yield), (ii) grain composition (nitrogen (N) and S contents) and quality (fatty acid (FA) composition and seed storage protein (SSP) accumulation) and (iii) germination characteristics (pre-harvest sprouting, germination rates and abnormal seedlings). Abscisic acid (ABA), soluble sugar contents and seed conductivity were also measured. HT and LS decreased the number of seeds per plant. SDW was less affected due to compensatory effects since the number of seeds decreased under stress conditions. While LS had negative effects on seed composition by reducing the FA contents and increasing the ratio S-poor SSPs (12S globulins)/S-rich SSPs (2S albumins) ratio, HT had positive effects by increasing S and FA contents and decreasing the C18:2/C18:3 ratio and the 12S/2S protein ratio. Seeds produced under HT showed high pre-harvest sprouting rates along with decreased ABA contents and high rates of abnormal seedlings. HT and LS restriction significantly accelerated germination times. High conductivity, which indicates poor seed storage capacity, was higher in HT seeds. Consistently, the lower ratio of (raffinose +stachyose)/sucrose in HT seeds indicated low seed storage capacity. We demonstrated the effects of HT and LS on grain and on germination characteristics. These results suggest that hormonal changes might control several seed characteristics simultaneously.